Economic capital : what it is and what every bank manager should know - Klaassen, Pieter; Eeghen, Idzard van. (Burlington, MA : Elsevier Finance, 2009)
The book presents new ways to define, measure, and implement management strategies by using recent examples, many from the sub-prime crisis. The authors also discuss the role of economic capital within the broader context of management responsibilities and activities as well as its relation to other risk management tools that are available to the modern risk manager. The book: explains ways to use economic capital in balancing risk and return; evaluates solutions to problems encountered in establishing an economic capital framework; emphasizes intuition; and, draws special attention to embedding risk modelling approaches within economic capital frameworks
Chapter 1: Measuring the Unexpected: Understanding Economic Capital -- Chapter 2: Show Me the Money: The Purpose of Economic Capital -- Chapter 3: You Manage What You Measure: Defining Economic Capital -- Chapter 4: Running the Numbers: Measuring Economic Capital -- Chapter 5: Facing Reality: Implementing Economic Capital -- Chapter 6: Team play: Economic Capital and its Context -- -- Chapter 7: What's Next? The Future of Economic Capital.
&#x000A
Includes bibliographical references and index.
&#x000A
oif 23/05/13
Loan
Keywords: Bank capital; Bank management; Banks and banking -- Risk management